Evolution of the Heme Biosynthetic Pathway in Eukaryotic Phototrophs - Cihlář, Jaromír (Jihočeská univerzita, 2018)
This thesis is devoted to the evolution of the heme biosynthetic pathway in eukaryotic phototrophs with particular emphasis on algae possessing secondary and tertiary red and green derived plastids. Based on molecular biology and bioinformatics approaches it explores the diversity and similarities in heme biosynthesis among different algae. The core study of this thesis describes the heme biosynthesis in Bigelowiella natans and Guillardia theta, algae containing a remnant endosymbiont nucleus within their plastids, in dinoflagellates containing tertiary endosymbionts derived from diatoms called dinotoms, and in Lepidodinium chlorophorum, a dinoflagellate containing a secondary green plastid. The thesis further focusses on new insights in the heme biosynthetic pathway and general origin of the genes in chromerids the group of free-living algae closely related to apicomplexan parasites.
Evolution of the Heme Biosynthetic Pathway in Eukaryotic Phototrophs
Keywords: Heme; biosynthesis; Pathway; Evolution; Eukaryotes; Phototrophs; Endosymbiosis; Heme; biosynthesis; Pathway; Evolution; Eukaryotes; Phototrophs; Endosymbiosis